Wedang Uwuh Business Management in Ketaon Village, Boyolali District - Savitri, Rosalina Sekar Ayu; Suyatmini, S (Proceedings International Conference on Education Innovation and Social Science, 2024)
The aim of this research is to find out how the wedang uwuh business is managed in Ketaon Village, Boyolali Regency. This research uses qualitative research. The data used in this research is primary data. Data collection techniques use observation, interviews and documentation. The number of respondents in this study was 1 person, namely the owner of the wedang uwuh business. Data analysis techniques use data reduction techniques, data presentation and drawing conclusions and verification. The results of the research show that the Human Resources management carried out by Pak Sri Handoyo's Wedang Uwuh Business is still taught individually or personally and is only based on employee performance. For financial management, just make simple bookkeeping reports such as cash in and out. Production management is in accordance with existing procedures. The marketing management of the Wedang Uwuh product is only assisted by the social media facility WhatsApp, introducing this product from home and at home, and relying on connections from the co-owners themselves.